DAKWAH EDUKATIF SEBAGAI INSTRUMEN PEMBENTUKAN KARAKTER RELIGIUS ANAK DI LINGKUNGAN MADRASAH INSIGHT DARI KKN SUMBERBENDO - Khoiriyah (DEVELOPMENT: Journal of Community Engagement, 2024)
This study examines how educative da’wah can effectively shape the religious character of children in madrasahs, particularly through the Community Service Program (KKN) in Sumberbendo. It addresses the increasing need for formal religious education that goes beyond teaching rituals or religious laws, focusing on developing strong spiritual and moral values from an early age. Educative da’wah is understood as an approach that combines clear communication, creativity, and local relevance, believed to be effective in instilling values such as honesty, responsibility, social care, and tolerance. Employing a qualitative case study method, this research includes direct participatory observation, in-depth interviews with madrasah teachers, religious leaders, parents, and students, as well as documentation of KKN activities. Data analysis uses thematic coding to identify factors supporting or hindering the implementation of educative da’wah and its impact on children's religious character development. The findings indicate that educative da’wah, through joint worship practices, value-based educational games, and contextually relevant religious discussions, enhances children's religious awareness and fosters tolerance, empathy, and discipline. However, challenges such as inadequate facilities, diverse family religious backgrounds, and limited time are noted as significant obstacles to optimal implementatio.